Gender and Grade DIF Analysis of Elementary School Students’ Ecological Awareness Instrument - I Nyoman Indhi Wiradika; Gede Surya Mahendra (STKIP Al Islam Tunas Bangsa dan HEPI, 2026)
The use of ecological awareness instruments in educational settings raises significant concerns regarding measurement fairness across different demographic groups. This study aims to identify items that exhibit differential item functioning (DIF) in an ecological awareness instrument administered to elementary school students. Data were collected from 623 elementary school students in Nusa Penida, consisting of 329 boys and 294 girls across Grades 4 to 6. The instrument was analyzed using Item Response Theory (IRT) with the Generalized Partial Credit Model (GPCM), and DIF was detected using the lordif package in R. Results indicate that six items exhibited gender-based DIF, predominantly in the environmental participation dimension, while five items showed grade-based DIF, primarily within the environmental knowledge dimension. Female students demonstrated higher levels of ecological awareness than male students across all grade levels. These findings highlight the importance of selecting items that are equally interpretable across gender and grade groups to ensure fair and valid assessment of ecological awareness in elementary schools.